Chem is Fun: Animation Learning Media Based on Quantum Learning on Atomic Structure - Sri Rejeki Dwi Astuti; Anggi Ristiyana Puspita Sari; Rizki Nor Amelia (Chemistry Education Department, 2021)
Good learning media are media that can facilitate students to understand the material. The selection of learning media must be in accordance with the characteristics of the teaching material. To facilitate explaining the atomic structure material that is abstract, we need a medium that can realize the material. This study aimed to develop an interactive animation learning media Chem is Fun based on quantum learning and determine the quality of the product. The development model used was the ADDIE model by adapting the development procedures, namely the analysis, design, development, and evaluation stages. This study involved one media expert, one material expert, three peer reviewers, and five reviewers to assess product quality. The instrument used in this study consisted of an advice sheet and a questionnaire. The results of the study state that the learning media product Chem is Fun based on quantum learning has good quality, so it can be used as a learning medium to help students' learning process on atomic structure material.